Some features of vocational school and ways to improve learning there - Jakavičius, V. (Psichologija, 1963)
This article examines some of the peculiarities of students' focus on a wide range of educational materials and also the impact of didactic measures on the level of knowledge absorption.Our studies have shown that teaching emphasis is different at vocational youth schools and some teachers need measures to get and maintain students' attention. The examination revealed that specific teaching materials were relatively easy for students to pay attention to, while abstract material did not grab their attention. The didactic means by which attempts were made to induce and maintain students' attention had a relatively large impact on younger students (up to 17), mastering abstract educational material. The older students (18-25 and older) saw somewhat improved results in learning factual material.Thus getting the students' attention and maintaining in within the confines of a vocational school, as shown by research, has great psychological and pedagogical implications and is one of the conditions for preparing students for educational attainment. However, in order to prepare students to actively absorb knowledge it is not enough to get their attention. In addition to this, studies have shown that vocational school specifics require the following:a) Ascertain students' existing knowledgeb) When possible eliminate gaps in knowledge (this is especially important if past and current topics overlap)c) Raise students' interest in the educational materiald) Promote self-confidence of students who for various reasons are lagging behind in scienceGetting the students' attention and preparing them to absorb knowledge is not a separate and independent link in the educational process. This takes place throughout the whole training process and possibly beyond. The didactic tools vary. Their selection at the vocational school primarily determines the specific composition of the students, i.e. age characteristics, life and production experience, learning motives, etc.
Keywords: educational materials; concentration; mastery of materia